Alcoholic and non-alcoholic fatty liver disease and associations with coronary artery calcification: evidence from the Kangbuk Samsung Health Study. Issue 9 (24th November 2018) - Chang, Yoosoo; Ryu, Seungho; Sung, Ki-Chul; Cho, Yong Kyun; Sung, Eunju; Kim, Han-Na; Jung, Hyun-Suk; Yun, Kyung Eun; Ahn, Jiin; Shin, Hocheol; Wild, Sarah Helen; Byrne, Christopher D
Abstract : Objective: Recent evidence suggests that alcoholic fatty liver disease (AFLD) and non-alcoholic fatty liver disease (NAFLD) may differentially affect risk of cardiovascular mortality. To investigate whether early liver disease due to AFLD or NAFLD have similar or dissimilar effects on risk of early coronary artery atherosclerosis, we have investigated the associations between AFLD and NAFLD and coronary artery calcium (CAC). Design: A cross-sectional study was performed in 105 328 Korean adults who attended a health check-up programme. CAC score was assessed using CT, daily alcohol intake was recorded as grams/day and liver fat by ultrasound. Logistic regression model was used to calculate ORs with 95% CIs for prevalent CAC. Results: Both NAFLD and AFLD were positively associated with CAC score. After adjusting for potential confounders, multivariable-adjusted OR (95% CIs) for CAC >0 comparing NAFLD and AFLD to the reference (absence of both excessive alcohol use and fatty liver disease) were 1.10 (95% CI 1.05 to 1.16) and 1.20 (95% CI 1.11 to 1.30), respectively. In post hoc analysis, OR (95% CI) for detectable CAC comparing AFLD to NAFLD was 1.09 (95% CI 1.01 to 1.17). Associations of NAFLD and AFLD with CAC scores were similar in both non-obese and obese individuals without significant interaction by obesity (p for interaction=0.088). After adjusting for homeostasis model assessment of insulin resistance and high-sensitivity C reactive protein, the associations between fatty liver disease and CAC scores remained statistically significant. Conclusion: In this large sample of young and middle-aged individuals, early liver disease due to NAFLD and AFLD were both significantly associated with the presence of coronary artery calcification.